Current prevalence of major depressive disorder in the general population from Bucaramanga, Colombia - Nubia L. Hernández; Adalberto Campo; Germán E. Rueda; Luis A. Díaz; Laura del Pilar Cadena (Universidad de Antioquia, 2010)
Major depressive disorder (m d d) is the disorder with the most important global burden in terms of disability-adjusted life years. Objetive: to determine the current prevalence of m d d in the general population in Bucaramanga, Colombia, and to explore the risk factors associated with them. Methodology: this is a cross-sectional survey with a population random sampling that involved 18-65 year-old people living in Bucaramanga. A psychiatric diagnosis of a m d d during last month was accomplished using Structured Clinical Interview for Axis I diagnoses (s c i d-i) according to the d s m-i v-t r criteria issued by the American Psychiatric Association. Results: a total amount of 266 people were selected (57,1% women). Their mean age were 37,4 years and the formal education years were 9,8. A total of 12,0% was unemployed, 56,1% had a stable couple, and 51,2% lived in medium socioeconomic strata. The prevalence of m d d was 16,5% (95% c i 12,3-21,6). A significant association was identified between the fact of not having a stable couple (p r = 2,11) and the and level of education (p r = 0,41, for 6-11 cursed years, and p r = 0,28, for 12 or more cursed years, compared to five or lesser years of schooling) and the m d d. Discussion: the current prevalence of m d d is high among adult general population from Bucaramanga. This implies the necessity to develop better strategies for an early detection and an integral treatment of m d d cases in order to decrease social and economical costs of m d d.